Sistem Pengelolaan Arsip Dinamis di Bagian Tata Usaha di Madrasah Aliyah Al-Kholafiyah Tekung - Aliyah, Himmatul; Herzegovina, Rani Nurul Laili (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The process of successfully, efficiently, and methodically managing archives through their production, use, and maintenance as well as their depreciation is known as a dynamic archive management system. The following are the goals of this study: 1) To provide an overview of Madrasah Aliyah Al-Kholafiyah Tekung's dynamic records management system in the administrative division. 2) To outline the challenges encountered in the administration division of Madrasah Aliyah Al-Kholafiyah Tekung when handling dynamic archives. 3) To explain how Madrasah Aliyah Al-Kholafiyah Tekung's administrative division overcame the limitations of dynamic archive management. Descriptive research is one of the qualitative research methodologies used in this study. Documentation, interviews, and observation were used as data gathering methods. The administrative department's dynamic records management system is described by this study. Creating, using, storing, preserving, and depreciating dynamic archives are all part of the administration section's dynamic archive management system at Madrasah Aliyah Al-Kholafiyah Tekung, according to the research's findings. 2) Using, storing, and maintaining dynamic archives are the activities that hinder the administration division of Madrasah Aliyah Al-Kholafiyah Tekung from managing dynamic archives. 3) The administration section of Madrasah Aliyah Al-Kholafiyah Tekung's dynamic archives management challenges can be resolved through the use, storage, and upkeep of dynamic archives.